Power! A field based testing resource for strength & conditioning personnel - Bonder, I.; Waller, M.; Tangeman, M.; Shim, A. (International Journal of Strength and Conditioning, 2025)
Power may be the most vital physical trait towards successful sport performance. Whether competing in team sports such as basketball and rugby; individual sports including track and field events, tennis, and golf; endurance based events encompassing cross country skiing, marathon running, and long distance swimming; or even tactical occupations, power development and maintenance is crucial to an athletes` success. The specific power component most vital to success should be identified, monitored, and tested to ensure continued development and/or maintenance throughout a competition calendar. By conducting a needs analysis, the specific contributions of power to a given sport can be determined. Equally important as knowing how to develop power, is also knowing what economic field based tests are available to accurately assess athletic development. The purpose of this article is to provide strength and conditioning coaches (SCC) across numerous levels/populations and having various levels of funding, with a brief overview, categorization and coaching resource for the vast array of field testing methods available to assess and monitor whole, upper, and lower body power.